2018
DOI: 10.4039/tce.2017.62
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and stability of populations of chewing lice (Phthiraptera: Amblycera and Ischnocera) infesting two species of woodpeckers (Aves: Piciformes: Picidae)

Abstract: The annual abundance of chewing lice (Phthiraptera) was recorded from 1996 to 2015 in Manitoba, Canada, on two species of woodpeckers (Piciformes: Picidae). Yellow-bellied sapsuckers (Sphyrapicus varius (Linnaeus)) were infested with Menacanthus pici (Denny) (Amblycera: Menoponidae) and Penenirmus auritus (Scopoli) (Ischnocera: Philopteridae); northern flickers (Colaptes auratus (Linnaeus)) were also infested with M. pici, as well as two other Ischnocera, Penenirmus jungens (Kellogg) and Picicola porisma Dalgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
(52 reference statements)
3
3
0
Order By: Relevance
“…The lowest previously observed values of PV for mean intensity were 0.3 for two species of lice on feral pigeons (Galloway and Lamb 2014), which suggests that temporal variation for mean intensity of lice on great horned owls is, in fact, remarkably low. Values of PV for louse prevalence on great horned owls at 0.21 and 0.34 were close to the average (0.28) of those observed for bird lice in Manitoba Lamb 2014, 2015b;Lamb and Galloway 2018).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The lowest previously observed values of PV for mean intensity were 0.3 for two species of lice on feral pigeons (Galloway and Lamb 2014), which suggests that temporal variation for mean intensity of lice on great horned owls is, in fact, remarkably low. Values of PV for louse prevalence on great horned owls at 0.21 and 0.34 were close to the average (0.28) of those observed for bird lice in Manitoba Lamb 2014, 2015b;Lamb and Galloway 2018).…”
Section: Discussionsupporting
confidence: 76%
“…In previous studies, lice on the same host showed speciesspecific PV and species with high abundance tended to have lower PV than less abundant species. As observed previously for chewing lice Lamb 2014, 2015b;Lamb and Galloway 2018), most of the temporal variation in louse abundance on great horned owls was accounted for by mean intensity rather than prevalence. Kurodaia magna and S. oculatus did show speciesspecific differences in PV for some population parameters, particularly prevalence and sex ratio, but were more similar than previously studied lice within multispecies louse communities on the same host.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…, Lamb et al. , Galloway and Lamb , Lamb and Boivin , b, Lamb and Galloway ). Many species have now been shown to exhibit characteristic density‐dependent processes that could lead to species‐specific levels of stability in the face of similar environmental variation (insects, Alyokhin et al.…”
Section: Discussionmentioning
confidence: 97%